An Investigation of Pakistani L2 HI Writers’ Perceptions of Previous Writing Experience in L2: Implications for Literacy Development in Pakistan for HIC - Haider, Ghulam (Richtmann Publishing, 2012)
Writing, unlike speaking, is not an ability we acquire naturally, even in our first language - it has to be taught. UnlessL2 HI Writers learners are explicitly taught how to write in the new language, their writing skills are likely to get left behind asalready their speaking skills are not naturally developed. But teaching writing is not just about grammar, spelling, or themechanics of the Roman alphabet. Learners also need to be aware of and use the conventions of the genre in the newlanguage. Case studies in second language (L2) writing with hearing students also reveal how difficult it is for non-nativeEnglish-speaking (NNES) students to write in English despite their time and effort invested in writing and high English languagetest scores. Present study explored H.I students’ needs and perceptions that would eventually lead to offer the right assistance.Extending the line of previous research, this study investigated the H.I students’ perceptions and views of an academic writingcourse designed by the Punjab Text Book Board.